Can the EU's new global strategy make a difference? Strengthening resilience in the Eastern Partnership countries. Issue 7 (3rd October 2021) - Kakachia, Kornely; Legucka, Agnieszka; Lebanidze, Bidzina
ABSTRACT: This article assesses the European Union's (EU) performance in promoting societal resilience in the Eastern Partnership countries (EaP) on examples of Georgia and Ukraine. We examine two approaches to external resilience-building employed by the EU: support for the sources of societal resilience (social trust, legitimacy of governance actors, design of governance institutions) and prevention of domestic and external risks. Our research shows that while Ukraine and Georgia possess a moderate degree of societal resilience both countries also suffer from a high exposure to domestic and external risks, making them dependent on external resilience-building support from the EU. Analysis of the EU's resilience-building agenda in Georgia and Ukraine shows a mixed record for the EU. While the EU managed to strengthen sources of resilience and alleviate domestic risks in both countries, it failed to mitigate geopolitical risks: leaving the window open for new conflicts and endangering the sustainability of its resilience agenda.